LARGE MAMMALS - Mohd Azlan, Jayasilan; Sally Soo, Kaicheen (UNIMAS Publisher and Natural History Publications (Borneo) Sdn. Bhd., 2023)
Protected areas, both on land and in water, are internationally recognised as bulwark against disruptive events, and it is believed that a wellmanaged protected area provides shelter for biodiversity. In Sarawak, protected areas are categorized into National Parks, Wildlife Sanctuaries, and Nature Reserves, each with different roles. National Parks and Nature Reserves are open to public, whereas access to Wildlife Sanctuaries is restricted.